Anthropology, by comparison - Gingrich, André; Fox, Richard G. (Richard Gabriel), 1939- (Routledge, 2002)
An international group of anthropologists take a fresh look at various neglected approaches to comparison and present new approaches that are relevant to the globalized world of the twenty first century.
Keywords: Ethnology -- Methodology.; Cross-cultural studies.; Cross-Cultural Comparison; Ethnologie -- Méthodologie.; Études transculturelles.; SOCIAL SCIENCE -- Anthropology -- Cultural.; POLITICAL SCIENCE -- Public Policy -- Cultural Policy.; SOCIAL SCIENCE -- Popular Culture.; Cross-cultural studies; Ethnology -- Methodology; Culturele antropologie.; Vergelijkend onderzoek.